Peningkatan Kualitas Pembelajaran Melalui Pelatihan Flash Card 3D Interaktif Berbasis Teknologi di SMA Negeri 2 Medan - Soraya, Ratna; Hadiani, Fitri; Andriany, Liesna; Pohan, Lisa Ariyanti; Kartika, Rika; Amalia, Nurfatima (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This study aims to enhance learning quality at SMA Negeri 2 Medan through training in the development of technology-based interactive 3D flash cards. The initiative responds to teachers’ and students’ need for more engaging learning tools that align with digital advancements. The training program was designed to give participants hands-on experience in creating and utilizing 3D flash cards, using visual design and augmented reality applications. The process emphasized a learning by doing approach, ensuring active involvement from planning to product evaluation. Data were gathered through observation, interviews, documentation, and assessment of participants’ work. The results reveal improved understanding among teachers and students regarding technology-based learning media, greater proficiency in 3D design applications, and better integration of 3D flash cards into classroom activities. Beyond fostering teacher creativity, the training also increased students’ motivation to learn. These findings suggest that digital technology, especially interactive 3D visual media, is effective in supporting secondary education. This training is expected to serve as a foundation for SMA Negeri 2 Medan to continue innovating in educational technology.